The Role of Corporate Governance in Controlling the Earnings Management Practices of Palestinian Shareholding Industrial Companies: A Field Study - Alkababji, Majdi (The Arab Journal of Administration, 2019)
The study aimed to demonstrate the role of commitment to the ingredients of corporate governance and its relationship to restrict the earnings management practices in Palestinian shareholding industrial companies, some boards of companies tend to earnings management practices through the influence of the measurement processes and accounting disclosure way that serves their interests, taking advantage of the flexibility in the international accounting standards to choose between the methods and policies of the accounting alternative. To achieve the objectives of the study the researcher was used Jones amended model (Jones, 1991), (Dechow, et al,1995-1996), which focuses on measuring the total accruals for the measurement of earnings management practices, corporate governance was measured through a variety of their ingredients proxy by ( Board Independence, Board Size, Board Meeting, Chief Executive Officer(CEO) Duality, Audit Committee Independence), also been used a group of control variables proxy by ( Firm Size, Leverage, Big 4 Companies (The sample of the study consist of all public shareholding industrial companies, which are about (13) companies, throughout the years 2012-2015. The results of the study revealed that industrial companies have been exercising earnings management during the years of the study, in addition to having variable relationships among corporate governance ingredients and earnings management. The researcher has offered a number of recommendations: The need to preserve the independence of the board of directors, the independence of audit committees and their members who have sufficient the competencies and experiences, there is no CEO duality at the company, in order to reduce the exploitation of managers and their negative practices to the earnings management, and increase the effectiveness of supervision of the financial reporting process.